The Impact of Technological Tools on Teaching - Alvarado López, Zulma Carolina; Mármol Cuéllar, Marvin Armando; Rodríguez Domínguez, Orquídea Guadalupe (2024)
This document contains information and experience about the specialization course named: The management of the virtual environment for Foreign Language Teaching and Learning. The fundamental things in order to learn online education and the application of it in online English Teaching. Some of the technological tools that the specialization course offers are: Google Meet, Google Classroom, etc. furthermore, the correct use and management of some technological tools more like: Edpuzzle, Kahoot, Canva, Powtoon, Flipgrid, Nearpod, Padlet and more. To make sure to use in online environment for academical purposes. Key words: E-Language Learning Environment ; Learning Management System ; Asynchronous e-Learning ; Synchronous e-Learning ; Online Learning ; Distance Learning.